SHORT CIRCUIT FAULT ANALYSIS IN THE ELECTRIC POWER DISTRIBUTION SYSTEM AT PT PLN (Persero) UP3 SOUTH MAKASSAR ULP KALEBAJENG USING ETAP - Nur Annisa Dewi Nayla; T Mangesa, Riana; Imran, Andi; Firdaus, Firdaus; Zulhajji, Zulhajji (Fakultas Teknik Universitas Negeri Makassar, 2023)
Short circuit fault analysis is needed to determine the amount of short circuit current flowing in a system. This study discusses the single-phase short-circuit current to the ground at the point where the disturbance occurs from the base of the network to the end of the Malewang feeder network. The purpose of this study was to determine the amount of short circuit fault current in the Electric Power Distribution System at PT PLN (Persero) UP3 South Makassar ULP Kalebajeng. This study used the ETAP program and manual calculations. The results of the study found that the contribution of the largest single-phase short-circuit fault current to the ground in the Malewang feeder occurred on Buses located at the base of the network close to the Substation, namely Bus 1 (Exim-Rec Kalaserena) of 0.311 kA, while thesmallest Buscontribution occurred on Buses located at the end of the network far from the Substation, namely Buses 14 (Bilonga) of 0.292 kA. From the results of the study, it can be concluded that the farther the interference bus is from the Substation, the greater the channel impedance. The greater the impedance, the smaller the short-circuit current.